2019
DOI: 10.3390/quat2010006
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary Variations in the South American Monsoon System as Inferred by Speleothems—New Perspectives Using the SISAL Database

Abstract: Here we present an overview of speleothem δ 18 O records from South America, most of which are available in the Speleothem Isotopes Synthesis and Analysis (SISAL_v1) database. South American tropical and subtropical speleothem δ 18 O time series are primarily interpreted to reflect changes in precipitation amount, the amount effect, and consequently history of convection intensity variability of convergence zones such as the Intertropical Convergence Zone (ITCZ) and the South America Monsoon System (SAMS). We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 57 publications
5
30
0
2
Order By: Relevance
“…Furthermore, Novello et al (2012) demonstrated that under such conditions, meridional Intertropical Convergence Zone (ITCZ) shifts become less influential in determining precipitation amounts in NEB. The variability of the first PC δ 18 O during the last millennium (Figure 3a) shows strong excursions toward negative values during the LIA, indicating enhanced precipitation over the western, south central, and southeastern portions of tropical South America, balanced by reduced precipitation in northeastern South America, consistent with results from previous studies (see references in Table 1 and Deininger et al, 2019). During the MCA, positive values indicate reduced precipitation, with even stronger positive values in the period preceding the onset of the MCA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, Novello et al (2012) demonstrated that under such conditions, meridional Intertropical Convergence Zone (ITCZ) shifts become less influential in determining precipitation amounts in NEB. The variability of the first PC δ 18 O during the last millennium (Figure 3a) shows strong excursions toward negative values during the LIA, indicating enhanced precipitation over the western, south central, and southeastern portions of tropical South America, balanced by reduced precipitation in northeastern South America, consistent with results from previous studies (see references in Table 1 and Deininger et al, 2019). During the MCA, positive values indicate reduced precipitation, with even stronger positive values in the period preceding the onset of the MCA.…”
Section: Discussionsupporting
confidence: 90%
“…Composite analyses and comparisons between the MC-PCA and the marine sediment record GeoB13813-4 (Perez et al, 2016), representing the integrated precipitation over the La Plata Basin drainage area, suggest a widening of the monsoon domain during the early LIA period (CE 1489to CE 1639. This result yields an alternative explanation to the spatiotemporal precipitation variability seen in the various (individual) proxy records, when compared to earlier studies which suggested that the SACZ or the monsoon axis was displaced southward during all the LIA (Apaéstegui et al, 2018;Bernal et al, 2016;Deininger et al, 2019;Novello et al, 2018).…”
Section: Discussionsupporting
confidence: 55%
“…Moving from the cave level (speleothems from the same cave [115]) to a regional level (speleothems from a cave system or nearby caves), the SISAL_v1 database and future versions provides a good opportunity for regional replication tests. On the one hand, if the records share common patterns, it might confirm a regional environmental signal, as in the case of e.g., South American Monsoon System [116]. On the other hand, trends and/or anomalies in stable isotope composition of speleothems occurring exclusively in an individual record may be owed to site specific factors.…”
Section: Regional Patterns In Carbon-and Oxygen Isotope Recordsmentioning
confidence: 91%
“…In subtropical South America these events remain uncertain (Deininger et al, 2019), thus climate reconstructions in the region are essential to understand the geography of the changes in hydrological regimes. Southeastern Brazil is directly influenced by the convective rain belt of the South Atlantic Convergence Zone (SACZ), from the western Amazon to southeastern Brazil and the South Atlantic.…”
Section: Introductionmentioning
confidence: 99%